AB0001 PLASMA miRNA PROFILE IN PATIENTS WITH HAND OSTEOARTHRITIS. (2nd June 2020) - Baloun, J.; Pekacova, A.; Kropackova, T.; Horvathova, V.; Prajzlerová, K.; Filková, M.; Pavelka, K.; Vencovský, J.; Šenolt, L.
Abstract : Background: MicroRNAs (miRNA) are short non-coding RNAs that can be involved in diverse physiological processes 1 . Aberrant miRNA profiles have been shown in various diseases including osteoarthritis (OA) 2 ; for instance, miR-21-5p or miR-140 are known for their altered expression in osteoarthritic cartilage 3, 4 . However, no screening of circulating miRNAs has been done in patients with hand OA (HOA) so far. Objectives: Our aim was to profile circulating miRNAs in plasma of patients with HOA in screening and validation cohort. Methods: We screened the expression of miRNA profiles in 4 patients with erosive (3 females, mean age=63.7±7 yrs) and 4 patients with non-erosive (3 females, mean age=62.4±6 yrs) HOA, and 4 control subjects (3 females, mean age=63.5±7 yrs). The validation cohort included 10 patients with erosive (7 females, mean age=67.5±7 yrs) and 10 patients with non-erosive (6 females, mean age=67.6±8 yrs) HOA, and 10 control subjects (8 females, mean age=64.3±8 yrs). Circulating miRNA screening were performed using TLDA and selected miRNAs were validated by qRT-PCR. Results: Profiling circulating plasma discovered 42 miRNAs from 754 analysed miRNAs with different concentration among subjects, including miR−23a−3p (1.7 fold), −222−3p (2.0 fold), and −30e−3p (13.0 fold) to be elevated in patients with HOA compared to control subjects. In addition, six miRNAs were distinctive between erosive and non-erosive HOA, e.g. hsa-miR-24-3p was 2.3 times lower and hsa-miR-576-5p was 3.4 times higher in erosive compared to non-erosive disease. Out of these selected miRNAs, qRT-PCR validated 42 miRNAs and confirmed 11 miRNAs (e.g., miR−23a−3p or –222-3p) with different concentration between patients and controls. However, no miRNAs distinguished between erosive and non-erosive HOA, although miR-101-3p (4.5 fold) and -320b (13.7 fold) almost reached statistical significance. Conclusion: Based on our study, we identified 11 miRNAs that may have a potential as biomarkers of HOA. However, further studies on larger cohorts are needed. References: [1]Krol, J., Loedige, I. & Filipowicz, W. The widespread regulation of microRNA biogenesis, function and decay. Nat. Rev. Genet. 11, 597–610 (2010). [2]Coutinho De Almeida, R. et al. RNA sequencing data integration reveals an miRNA interactome of osteoarthritis cartilage. Ann. Rheum. Dis. 78, 270–277 (2019). [3]Wang, X. et al. MicroRNA-21-5p as a novel therapeutic target for osteoarthritis. Rheumatology (Oxford). 58, 1485–1497 (2019). [4]Swingler, T. E. et al. The function of microRNAs in cartilage and osteoarthritis. Clin. Exp. Rheumatol. 37, 40–47 (2019). Acknowledgments: This work was supported by the project AZV no. NV18-01-00542 and MHCR No. 023728. Disclosure of Interests: Jiří Baloun: None declared, Aneta Pekacova: None declared, Tereza Kropackova: None declared, Veronika Horvathova: None declared, Klára Prajzlerová: None declared, Mária Filková: None declared, Karel Pavelka Consultant of: Abbvie, MSD, BMS, Egis, Roche, UCB, Medac, Pfizer, Biogen, Speakers bureau: Abbvie, MSD, BMS, Egis, Roche, UCB, Medac, Pfizer, Biogen, Jiří Vencovský: None declared, Ladislav Šenolt: None declared